Increased instruction hours and the widening gap in student performance - Mathias Huebener; Susanne Kuger; Jan Marcus (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
Do increased instruction hours improve the performance of all students? Using PISA scores of students in ninth grade, we analyse the effect of a German education reform that increased weekly instruction hours by two hours (6.5 percent) overalmost five years. In the additional time, students are taught new learning content. On average, the reform improves student performance. However, treatment effects are small and differ across the student performance distribution. While low-performing students do not benefit, high-performing students benefit the most. The findings suggest that increases in instruction hours can widen the gap between low- and high-performing students.
Keywords: I21; I24; I28; D04; J24; 330; instruction time; student achievement; PISA; G8-high school reform; quantile regressions; curriculum; difference-in-differences